Exosomes derived let-7f-5p is a potential biomarker of SLE with anti-inflammatory function - Yi-jing Liu; Hai-bing Miao; Shu Lin; Zhen Chen (Non-coding RNA Research)
This study found that in patients with SLE (n = 5), lethal (let)-7f-5p expression was significantly downregulated in peripheral blood mononuclear cells. Further, high-throughput RNA sequencing was used to mine the differential transcriptome expression in renal tissue exosomes of systemic lupus erythematosus (SLE)-prone mice, and bioinformatics was utilized to analyze non-coding RNAs and coding RNAs in exosomes for their possible roles in SLE. In renal tissues of MRL/lpr SLE-prone mice with exosomes and Pristane-induced SLE mice, we also demonstrated aberrant expression levels of microRNA (miRNA) let-7f-5p. Meanwhile, in the macrophage inflammation model, the expression levels of let-7f-5p were downregulated, that of guanylate binding protein (Gbp2 and Gbp7) were upregulated, and the inflammatory state of macrophages was alleviated following transfection with the let-7f-5p mimic. Co-culturing mesenchymal stem cells with a macrophage model of inflammation resulted in increased let-7f-5p expression and downregulated inflammatory factors, Gbp2 and Gbp7 expression in macrophages. Dual luciferase reporter gene assays confirmed that let-7f-5p directly binds to the 3′ UTR of Gbp7 to regulate its expression. Let-7f-5p regulation of the Gbp family is involved in SLE pathogenesis and is a biomarker associated with the inflammatory response with potential clinical applications.